If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 14 = -38 + -7x Reorder the terms: 14 + 6x = -38 + -7x Solving 14 + 6x = -38 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 14 + 6x + 7x = -38 + -7x + 7x Combine like terms: 6x + 7x = 13x 14 + 13x = -38 + -7x + 7x Combine like terms: -7x + 7x = 0 14 + 13x = -38 + 0 14 + 13x = -38 Add '-14' to each side of the equation. 14 + -14 + 13x = -38 + -14 Combine like terms: 14 + -14 = 0 0 + 13x = -38 + -14 13x = -38 + -14 Combine like terms: -38 + -14 = -52 13x = -52 Divide each side by '13'. x = -4 Simplifying x = -4
| -11-(-n+5)= | | 8n+10=66 | | 6n-13=29 | | 163-6x=4x+23 | | 84-3x=10x+19 | | -5(10-4m)+4(-8m-4)= | | 3.2x+x=2.2x+x | | -5a=-52 | | 7k+5+4k-3= | | 2x+8=x+4 | | 6p+10p+4= | | 17=n-27 | | 5x+31=13x-49 | | 11xy+4y^2-6xy+10y^2-12= | | 5+10y=9y-9 | | 0=-9(y+5) | | 7x+5+4x+8= | | 6p=5p+9 | | 3(x+2.59)=2x | | n+18=16 | | -5p-8+3-p= | | 6x+26=13x-37 | | 7+5y=4y-4 | | 5v+8+9v+7= | | 9(d+-1)+d=11 | | k^2-3k-8=0 | | 9(b-1)+b=11 | | 14+10y=2y-2 | | -v-3v+15= | | 7x+8=8x-20 | | 3(-z+6)+2z=-18 | | b-3-2b= |